2019
DOI: 10.1039/c8nr08607a
|View full text |Cite
|
Sign up to set email alerts
|

Bio-interfactants as double-sided tapes for graphene oxide

Abstract: We present a substrate-independent approach for preparing multisandwich films based on thermally reduced Graphene Oxide which gets strongly attached by bio-interfactants using a layer-by-layer aqueous dipping process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 83 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…In this study, we present a new surface immobilization strategy for AMPs with or without −3,4-dihydroxyphenylalanine (DOPA) in their sequence which profits from using laccase as a bio-interfactant. 26 The antimicrobial peptide used for immobilization is based on the peptide Tet-124 sequence KLWWMIRRW, previously synthesized by Hilpert et al 22 This peptide showed partial inhibition of Pseudomonas aeruginosa . Applying the adhesion mechanism of mussel foot proteins, we have modified the AMP sequence adding glycine-(4-bromophenylalanine)-(3,4-dihydroxyphenylalanine)-glycine to the original sequence reported, thus obtaining KLWWMIRRW-G-BrPh-DOPA-G.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we present a new surface immobilization strategy for AMPs with or without −3,4-dihydroxyphenylalanine (DOPA) in their sequence which profits from using laccase as a bio-interfactant. 26 The antimicrobial peptide used for immobilization is based on the peptide Tet-124 sequence KLWWMIRRW, previously synthesized by Hilpert et al 22 This peptide showed partial inhibition of Pseudomonas aeruginosa . Applying the adhesion mechanism of mussel foot proteins, we have modified the AMP sequence adding glycine-(4-bromophenylalanine)-(3,4-dihydroxyphenylalanine)-glycine to the original sequence reported, thus obtaining KLWWMIRRW-G-BrPh-DOPA-G.…”
Section: Introductionmentioning
confidence: 99%